Improving Service Quality with the SERVQUAL Method and Linear Programming Optimization at a Transportation Provider Company - Rizkiyah, Ega Rizkiyah; Supriyanto, Hari Supriyanto; Dharaka, Kumara Pinasthika Dharaka; Erlangga, Dicky Erlangga (JURNAL TEKNIK INDUSTRI, 2025)
The rapid growth of the technology industry poses significant challenges for transportation providers in maintaining service quality, particularly in addressing the gap between customer expectations and perceptions and ensuring efficient resource management. This study explores factors influencing service quality in Malaysian transportation provider companies using the SERVQUAL method, quality function deployment (QFD), and linear programming optimization. Key objectives include identifying issues in the TPM application service process, measuring gaps between customer perceptions and expectations, identifying critical service attributes using importance-performance analysis, and prioritizing technical responses to improve service quality using linear programming optimization. Based on root cause analysis, importance-performance mapping, and the house of quality framework, the study identified four key recommendations: updating standard operating procedures (SOPs) and monitoring service issues, providing driver training on methods and skills, implementing stricter driver selection criteria with a focus on code of conduct compliance, and developing an improved application interface for better customer location accuracy. These measures aim to enhance the efficiency and effectiveness of services, ensuring better alignment with customer needs and expectations while addressing critical operational challenges. By bridging the service quality gap, this research provides actionable insights to support continuous improvement in the Transportation Provider Company from Malaysia.